Pengaruh Motivasi Dan Kepemimpinan Terhadap Kinerja Pegawai Pada Dinas Pemberdayaan Masyarakat Dan Desa (DPMD) Provinsi Bengkulu - Edo Sandra; Ermy Wijaya; Andriyani Prawitasari (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Employee performance is the quality and number of individual consequences or combinations in exclusive actions caused by the characteristic capacity obtained from learning interactions and to perform better. The purpose of the study was to determine the effect of work discipline on employee performance at the Bengkulu Province Office of Community and Village Empowerment (DPMD), to determine the effect of work motivation on employee performance at the Bengkulu Province Office of Community and Village Empowerment (DPMD). This study aims to determine the effect of work discipline and work motivation on employee performance at the Bengkulu Province Office of Community and Village Empowerment (DPMD). The sample in this study was 44 employees, data collection using questionnaires and data analysis methods used multiple linear regression, determination test, and hypothesis testing. The results for the multiple regression equation show a positive regression direction with the equation Y = 9,747 + 0,897 (X1) + 0,832 (X2) + e, which means that if there is an increase in work discipline and work motivation, the performance of employees in the community and village empowerment office (DPMD) Bengkulu Province will also increase. Work discipline has a significant effect on employee performance in the Bengkulu Province Community and Village Empowerment Office (DPMD) because the value of ttable (2,954 < 1.677) and a significance value of 0.004 < from 0.050. Work motivation has a significant influence on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD) because the value of ttable (2,525 <1,677) and a significance value of 0.014 < from 0.050. The test results conclude that there is a significant influence between work discipline and motivation on employee performance at the Bengkulu Province Community and Village Empowerment Office (DPMD) together because the F arithmetic value > F table (154.995 > 3.133) with a significant value of 0.000 < 0.05.